2018
DOI: 10.1177/1049909117751419
|View full text |Cite
|
Sign up to set email alerts
|

It’s All About Communication: A Mixed-Methods Approach to Collaboration Between Volunteers and Staff in Pediatric Palliative Care

Abstract: Communication can be considered a key factor in successful collaboration between volunteers and staff. Because many patients in pediatric palliative care units are not able to communicate verbally, good information flow between volunteers and staff is crucial for ensuring quality patient care. Moreover, communication is the key to establishing a team philosophy by clarifying roles and building relationships between volunteers and staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Several studies have explored volunteer task performance, training, motivation, economic value and turnover rates (Burbeck et al, 2014;Claxton-Oldfield & Claxton-Oldfield, 2012;Morris, Payne, Ockenden, & Hill, 2017;Morris et al, 2013;Vanderstichelen, Houttekier, et al, 2018). However, with exception of a few studies that consider volunteer involvement -conceptualised mainly as volunteer presence -in palliative care (Candy, France, Low, & Sampson, 2015;Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, 2019c) and volunteerprofessional collaboration in palliative care (Meyer, Schmidt, Zernikow, & Wager, 2018;Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, 2019a;Wittenberg-Lyles, Parker Oliver, Demiris, & Regehr, 2010), the literature hitherto lacks insights into the wide variation of volunteers active in palliative care and into how volunteers are integrated into health services and care provision. Most studies limit their focus to volunteers in dedicated palliative care services (Candy et al, 2015;Hotchkiss, Unruh, & Fottler, 2014;Mundle, Naylor, Weaks, & Buck, 2013;Pesut, Hooper, Lehbauer, & Dalhuisen, 2014;Wilson et al, 2005), while research has, for instance, suggested that home-care services, sitting services and -to a lesser extent -oncology wards and nursing homes have volunteers who perform several palliative care-related tasks (Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, 2019b;Vanderstichelen et al, 2019c;Vanderstichelen, Houttekier, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored volunteer task performance, training, motivation, economic value and turnover rates (Burbeck et al, 2014;Claxton-Oldfield & Claxton-Oldfield, 2012;Morris, Payne, Ockenden, & Hill, 2017;Morris et al, 2013;Vanderstichelen, Houttekier, et al, 2018). However, with exception of a few studies that consider volunteer involvement -conceptualised mainly as volunteer presence -in palliative care (Candy, France, Low, & Sampson, 2015;Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, 2019c) and volunteerprofessional collaboration in palliative care (Meyer, Schmidt, Zernikow, & Wager, 2018;Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, 2019a;Wittenberg-Lyles, Parker Oliver, Demiris, & Regehr, 2010), the literature hitherto lacks insights into the wide variation of volunteers active in palliative care and into how volunteers are integrated into health services and care provision. Most studies limit their focus to volunteers in dedicated palliative care services (Candy et al, 2015;Hotchkiss, Unruh, & Fottler, 2014;Mundle, Naylor, Weaks, & Buck, 2013;Pesut, Hooper, Lehbauer, & Dalhuisen, 2014;Wilson et al, 2005), while research has, for instance, suggested that home-care services, sitting services and -to a lesser extent -oncology wards and nursing homes have volunteers who perform several palliative care-related tasks (Vanderstichelen, Cohen, Van Wesemael, Deliens, & Chambaere, 2019b;Vanderstichelen et al, 2019c;Vanderstichelen, Houttekier, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of integration is collaborationddifferent parties assuming complementary roles and working cooperatively together, sharing responsibility for problem-solving, and making decisions to formulate and carry out plans. 26 Although much is known about nurse-physician collaboration in patient care, 26e29 hitherto studies on volunteer-professional collaboration have been limited to pediatric PC 30 or hospice team meetings. 31 Literature has shown volunteer care to be complementary to professional care 21,22,32 but not how this actually and potentially translates to volunteerprofessional collaboration in practice.…”
Section: Introductionmentioning
confidence: 99%
“…According to international studies, the factors needed to address the sense of loss experienced by volunteers in the field of pediatric palliative care are: 1) basic education related to pediatric palliative care with detailed explanations of the field and roles of the volunteer to enhance their understanding [13,14] and 2) meaningful feedback including active communication with employees, acknowledgement of the value of volunteer activities, and respect for volunteers to help them find the meaning of positive life [15]. However, there are few Korean studies on volunteer activities in the field of pediatric palliative care.…”
Section: Introduction 1 Backgroundmentioning
confidence: 99%
“…However, there are few Korean studies on volunteer activities in the field of pediatric palliative care. Although the impact of education for hospice volunteers has been investigated [13,14], it was limited to adult hospice care, and the characteristics of volunteer activities in pediatric palliative care were not discussed. Pilot projects in pediatric palliative care have only recently started in Korea, and only limited data has been accumulated.…”
Section: Introduction 1 Backgroundmentioning
confidence: 99%